2014
DOI: 10.14238/pi54.1.2014.62-6
|View full text |Cite
|
Sign up to set email alerts
|

Soy-based infant nutrition: a review

Abstract: Dietary consumption of soy varies worldwide.In Asia, people traditionally consume largequantities of soy, while in Europe, soy is notpart of the traditional or daily eating habits.The USA is a major soy producer. The mean intake ofisoflavones by an adult is 8 - 50 mg/day in Asia but only0.5 - 3.5 mg/day in the Western world.1 The soy intakeof a vegetarian is 3 - 12 mg/day and a vegan achievesan intake of 15-60 mg/day.2In the early 1900s, soy-protein preparationswere the only option for the treatment of cow's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Another study revealed a similar evidence that they found no differences in terms of growth pattern, serum albumin, and hemoglobin levels between infants who consumed soya milk and those were initially breastfed and then weaned to cow's milk formula in their first year of life [ 11 ]. A review by Vandenplas and Hegar [ 12 ] also highlighted the difference in opinions regarding the adverse effects of soy formula and possible option for infants who are unable to breastfeed and cannot tolerate cow's milk. There has not been any study in Indonesia that particularly discussed the effect of soya milk on infant growth development.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed a similar evidence that they found no differences in terms of growth pattern, serum albumin, and hemoglobin levels between infants who consumed soya milk and those were initially breastfed and then weaned to cow's milk formula in their first year of life [ 11 ]. A review by Vandenplas and Hegar [ 12 ] also highlighted the difference in opinions regarding the adverse effects of soy formula and possible option for infants who are unable to breastfeed and cannot tolerate cow's milk. There has not been any study in Indonesia that particularly discussed the effect of soya milk on infant growth development.…”
Section: Introductionmentioning
confidence: 99%